2022
DOI: 10.1097/iyc.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Latinx Mothers' Experiences With Linkage to Early Intervention

Abstract: This study explored the experiences and perspectives of Latinx mothers of children younger than 3 years who had participated in a developmental screening initiative provided by 2 Federally Qualified Health Centers in an urban setting, had positive developmental screenings, and were referred to early intervention (EI) services. A 2-phase mixed-methods explanatory design was implemented in English and Spanish. In Phase 1, a telephone survey was conducted with 62 parents. In Phase 2, qualitative semistructured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These researchers noted that early childhood personnel did not regularly use higher level culturally responsive evaluation practices, such as asking families about their expectations for the testing process or about their values and hopes for their children (Steed & Stein, 2021). Another recent study found that while most White and Latina mothers felt that their child's initial evaluation was accurate, Latina mothers reported more challenges during the initial evaluation and barriers to accessing early intervention services (Quebles et al, 2022). More information is needed to understand how EI and ECSE professionals nationally are utilizing culturally and linguistically responsive practices during the initial evaluation, in recognition of the importance of the evaluation in accurately identifying all young children for EI/ECSE and connecting them quickly to services.…”
Section: Culturally and Linguistically Responsive Evaluation Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers noted that early childhood personnel did not regularly use higher level culturally responsive evaluation practices, such as asking families about their expectations for the testing process or about their values and hopes for their children (Steed & Stein, 2021). Another recent study found that while most White and Latina mothers felt that their child's initial evaluation was accurate, Latina mothers reported more challenges during the initial evaluation and barriers to accessing early intervention services (Quebles et al, 2022). More information is needed to understand how EI and ECSE professionals nationally are utilizing culturally and linguistically responsive practices during the initial evaluation, in recognition of the importance of the evaluation in accurately identifying all young children for EI/ECSE and connecting them quickly to services.…”
Section: Culturally and Linguistically Responsive Evaluation Practicesmentioning
confidence: 99%
“…While the population of children and families seeking and receiving early intervention and preschool special education services is increasingly culturally and linguistically diverse, the early intervention (EI) and early childhood special education (ECSE) workforce continues to remain largely White, female, and English speaking (Bureau of Labor Statistics and U.S. Department of Labor, 2018). Cultural, racial, and linguistic differences between children, families, and EI and ECSE professionals may present barriers on both sides to communicating about the child’s development, sharing concerns, and successfully linking the child to EI or ECSE services (Quebles et al, 2022).…”
mentioning
confidence: 99%